MEMS Resonator Q-factor microcontroller based measurement system / Ahmad Afdhaluddin Mohammad Aris - Mohammad Aris, Ahmad Afdhaluddin (2013)
This paper presents the hardware and algorithm of Q-factor for MEMS Resonator using microcontroller-based measurement system. Conventionally, the characterization of Micro-Electro-Mechanical System (MEMS) resonator required bigger equipment such as oscilloscopes and function generators for analysis. The purpose of this project is to design a simplified system to characterize MEMS Resonator with improve portability. The design and development of signal generator and display system will be based on microcontrollers. Instead of manual data collection and characterization of the signal, the system shall be able to calculate the resonance frequency and calculate the quality factor of the MEMS Resonator. The design of signal generator will be based on sin(x) algorithm to produce digital library to the output. The microcontroller is able to log data time/cycle when signal sampling crosses zero line. The frequency and amplitude can be measured based on the time record and the biggest value of sampling data. Validating against measured value using conventional laboratory equipment, the natural frequency and quality factor obtained has 0.67% and 20% error.